2001
DOI: 10.1089/089771501316919111
|View full text |Cite
|
Sign up to set email alerts
|

Strain and Model Differences in Behavioral Outcomes after Spinal Cord Injury in Rat

Abstract: Spinal cord injury (SCI) results in loss of function below the level of injury and the development of chronic central pain (CCP) syndromes. Since different strains may develop and express chronic pain behaviors differently, we evaluated behavioral outcomes (locomotor recovery and the development of mechanical and thermal allodynia) in three commonly used strains of rats (Long-Evans, Wistar, and Sprague-Dawley) using two models of SCI. The two models examined were contusion at T10 (NYU impactor, 12.5 mm height)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
71
0
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 58 publications
10
71
0
6
Order By: Relevance
“…In this study, the onset of excessive grooming behavior was slower in SD males than LE males, but the intensity of excessive grooming was greater in SD males. These results agree with previous reports related to the response to injury that show that SD rats exhibit significantly greater spontaneous pain, in addition to significantly greater mechanical and cold allodynia compared to LE rats (Yoon et al, 1999;Mills et al, 2001). The pattern of increase in neuronal activity of limbic structures in the present study may underlie the enhancement of these neuropathic behaviors in the SD strain after spinal injury.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, the onset of excessive grooming behavior was slower in SD males than LE males, but the intensity of excessive grooming was greater in SD males. These results agree with previous reports related to the response to injury that show that SD rats exhibit significantly greater spontaneous pain, in addition to significantly greater mechanical and cold allodynia compared to LE rats (Yoon et al, 1999;Mills et al, 2001). The pattern of increase in neuronal activity of limbic structures in the present study may underlie the enhancement of these neuropathic behaviors in the SD strain after spinal injury.…”
Section: Discussionsupporting
confidence: 93%
“…The greater baseline activity in the SII, AD, BLA, and PVN of the LE may explain, in part, published reports that LE rats perform better in cognitive tasks (Lindner and Schallert, 1988;Tonkiss et al, 1992;Andrews et al, 1995;Harker and Whishaw, 2002), have higher baseline levels of locomotor activity (Aulakh et al, 1988;Onaivi et al, 1992;van Lier et al, 2003), and show less reactivity to external stimuli (Glowa and Hanson, 1994;Acri et al, 1995;Faraday, 2002). In addition, LE rats are more sensitive to painful stimuli, indicated by lower baseline responses to painful mechanical and thermal stimuli applied to the hindpaw (Mills et al, 2001). It is possible that the differences in basal forebrain activation shown in our study may be in part responsible for differences in behavioral response reported by others.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Because rat strain and substrain differences influence the magnitude of respiratory LTF (Fuller et al, 2001b) and the severity of motor and sensory impairment after SCI (Gorman et al, 2001;Mills et al, 2001), the choice of rat strain could influence the ability of intermittent hypoxia to induce pLTF after chronic SCI. To account for this possibility, we studied both inbred Lewis (LW) and outbred Sprague Dawley (SD) rats.…”
Section: Methodsmentioning
confidence: 99%